Intra- and inter- observer reliability of the Canyoning Assessement Tool - Sarmento, DL.; Brandão, A.; Gonçalves, L.; Pereira, J.; Clemente, FM. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The numerous technical manuals or technical training does not guarantee a good technical level. Objective: Validate an instrument for evaluating the rope manoeuvres skills for canyoning - level I. Methods: 28 individuals, including beginners (<3 years of experience), and experienced practitioners (≥ 3 years of experience) in this sport. These presented an average age of 27.5 +- 7.89 years. The technical execution was recorded in video for further evaluation. This was done by three observers, all experienced in canyoning where two of them teaching this sport at University. The evaluation was replicated later over 20 days. Results: The results had good reliability levels, in the intra- and inter-class analyses, as in the test/re-test analysis. The Final Score variables present excellent reliability among the three observers. Conclusion: After analysing the results, we concluded that the CAT (Canyoning Assessment Tool) is a reliable instrument for evaluation skills in rope manoeuvres in canyoning.